2021
DOI: 10.1186/s12883-021-02187-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival in amyotrophic lateral sclerosis: a nationwide, Danish cohort study

Abstract: Introduction Amyotrophic lateral sclerosis (ALS) is a progressive motor neuron disease with great heterogeneity. Biological prognostic markers are needed for the patients to plan future supportive treatment, palliative treatment, and end-of-life decisions. In addition, prognostic markers are greatly needed for the randomization in clinical trials. Objective This study aimed to test the ALS Functional Rating Scale-Revised (ALSFRS-R) progression rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…Previous studies have identified ΔFS as a biomarker of ALS survival collected cross‐sectionally at baseline 6,18,22,23 . The present findings are in concordance with previous studies, confirming that a faster rate of disease progression at baseline (ΔFS ≥1.1) is associated with greater functional disability and muscle weakness.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have identified ΔFS as a biomarker of ALS survival collected cross‐sectionally at baseline 6,18,22,23 . The present findings are in concordance with previous studies, confirming that a faster rate of disease progression at baseline (ΔFS ≥1.1) is associated with greater functional disability and muscle weakness.…”
Section: Discussionsupporting
confidence: 92%
“…The limitations inherent to the ALSFRS-R also influence composite end points, and post hoc analysis may become necessary to reconstruct the single score effects 36. Survival and ALSFRS-R scores are independently interrelated37 and it remains to specifically assess whether and to what extent combining these two measures provide a basis for medical decision-making 38. While symptom progression influences both functional decline and survival, these two end points are differently impacted by the possibility that a patient completes the study.…”
Section: Discussionmentioning
confidence: 99%
“…Age of onset, region of onset and El Escorial criteria are prognostic factors [4,32,33] but were not found to be influential in our study concerning any progression group, regardless of their differences between groups (Table 5). Although progression rate is a good prognostic marker of survival [10,34], the discordance between predictors of survival and disease progression has been noted before [24,[35][36][37][38]. In fact, the functional decline based on ALSFRS-R total score is strongly associated with survival but is not a strong predictor [36], which is evidenced by some of the most severely disabled patients being amongst the longest survivors.…”
Section: Discussionmentioning
confidence: 99%